Unholy war - Esposito, John L. (Oxford University Press, 2002)
The devastating September 11 attacks on the World Trade Center and the Pentagon left us stunned, angry, and uncomprehending. As it became clear that these horrifying acts had been committed in the name of Islam, we struggled to understand how religion could be used to justify the slaughter of innocents. The media, the government, and ordinary citizens alike sought answers to questions about Islam and its adherents. Who are the Muslim extremists who perpetrate such deeds? Why do they hate us? What do they hope to achieve? Does Islam really teach that such terrorists are holy warriors who will be rewarded with everlasting bliss?